(untitled) (Nigerian Journal of Technology, 2015)
This study was carried out to evaluate the effect of bagasse ash on the California bearing ratio of lateritic soil. Laboratory tests were performed on the natural and bagasse ash treated soil samples in accordance with BS 1377 (1990) and BS 1924 (1990) respectively. Treated specimens were prepared by mixing the soil with bagasse ash in steps of 0, 2, 4, 6 and 8 % by weight of dry soil and contaminating it with used oil in steps of 0, 2, 4, and 6 % by weight of dry soil. The preliminary laboratory investigation carried out on the natural lateritic soil shows that it falls under Silt-Clay material of Group A-6 using AASHTO classification and inorganic clay material of low to medium plasticity CL according to Unified Soil Classification System (USCS). The specific gravity of the soil samples decreased from 2.61 for the natural soil to 2.48 at 8 % bagasse ash content and to 2.16 and 2.11 at 6 %oil / 0 %BA and 6 %oil / 8 %BA contents respectively. The liquid and plastic limits increased from 36.32 and 21.30 % respectively to peak values of 38.00 and 21.54 % at 2 % bagasse ash content for all oil contents. The maximum dry density (MDD) of the soil increased from 1.48 Mg/m3 for the natural soil to peak value of 1.49 Mg/m3 at 8 % bagasse ash content for all oil contents. The Optimum Moisture Content (OMC) increased from a value of 18.5 % for the natural soil to 19.0 % at 2 and 4 % bagasse ash contents and then after decreased. The unsoaked California bearing ratio values from 4 %BA content and above met the minimum CBR value of 30% specified by (BS 1990) for materials suitable for use as base course material when determined at MDD and OMC. However, the highest CBR value of 62 % recoded at 8 % BA content failed to meet the 80 % CBR value recommended by the Nigerian general specification (1997) for cement stabilization. Oil contamination resulted in reduced CBR values (strength) in lateritic soils. http://dx.doi.org/10.4314/njt.v34i2.2